2017
DOI: 10.5272/jimab.2017233.1697
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Postoperative Pain After Extraction of Impacted Mandibular Third Molars and Administration of Preemptive Analgesia

Abstract: Objective: Postoperative pain control after extraction of impacted mandibular third molars is important for patients because of the effect of pain symptoms on the healing process and quality of life. The objective of this study is to make a quantitative and qualitative assessment of the postoperative pain in patients to whom preemptive analgesia was administered.Material and Methods: This is a randomised, placebo-controlled study in 80 patients who underwent surgical removal of impacted mandibular third molars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…Preemptive analgesia is a controversial topic. Differences between experimental models, including different routes of administration, drug combinations, time of postoperative pain evaluation, types of surgery, [19]. There are numerous techniques for analgesic treatment of postoperative pain, but the interest in recent years has been focused on the preemptive analgesia.…”
Section: Resultsmentioning
confidence: 99%
“…Preemptive analgesia is a controversial topic. Differences between experimental models, including different routes of administration, drug combinations, time of postoperative pain evaluation, types of surgery, [19]. There are numerous techniques for analgesic treatment of postoperative pain, but the interest in recent years has been focused on the preemptive analgesia.…”
Section: Resultsmentioning
confidence: 99%
“…Prevention and management of these processes is an important objective in dentistry. According to literature, a scientifically justified drug for controlling pain and inflammation is nimesulide, which is due to its high clinical effectiveness, safety profile and short onset of action [ 25 , 26 , 27 , 28 ]. According to the results of our survey, dentists most frequently use nimesulide to manage inflammation following dental interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Like the quantitative optical microscopy we used in this work, laser diffraction analysis is a direct method of studying the size distribution of nimesulide API particles. But this method requires expensive specialized equipment [ 25 ], highly qualified and specially trained personnel, complex preparation for the final analytical process of the test, so it is not rapid and easy to perform. Based on this, in our opinion, laser diffraction analysis will be difficult to use as a "generally accessible" method of pilot detection of abnormal lots of generic drugs nimesulide on the market, in contrast to the proposed method of pharmacopoeial quantitative optical microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…The pain assessment was carried out 6 hours post-dental extraction and every 12 h thereafter on the same day of extraction and the following two days, because the highest pain point is between 6 to 8 h after extraction and intensity of pain has been shown to reach its maximum in the first 24 h [5,6]. The pain assessment was recorded by the patient via a questionnaire (data collecting sheet) using the Visual Analogue Scale (VAS).…”
Section: Assessment Of Post-operative Dental Painmentioning
confidence: 99%
“…A recent study indicated that the intensity of pain reaches its maximum score in the first 24 h after surgical tooth extraction using the McGill Pain Questionnaire [5]. The highest pain point occurs between 6 and 8 h after extraction with conventional local anesthetic techniques, as a result of trauma to the hard and soft tissues caused by surgical dental extraction.…”
Section: Introductionmentioning
confidence: 99%